The Effect of Box Jump, Box Shuffle, and Squat Jump Training on Speed in Badminton UKM Athletes, State University of Malang - Ahmad Muttaqin Darussalam; Mahmud Yunus; Heri Purnama Pribadi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2023)
Speed is a basic biomotor component that is needed in badminton. Speed is the ability to perform movements in the minimum time and move the body as quickly as possible. One of the speed exercises in badminton is box jump, box shuffle, and squat jump exercises. This study aims to determine the effect of the box jump, box shuffle, and squat jump exercises on speed in UKM Badminton athletes at the State University of Malang. The method in this study used the Pre-Experimental One Group Pretest-Posttest. In this study, 15 athletes were used as subjects, and the training program was carried out for 6 weeks. The results of the analysis show that there was a significant increase in the speed between the pretest and posttest (p<0.001). Concluded that box jump, box shuffle, and squat jump training affect the speed of UKM Badminton athletes at Malang State University.